(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The standard of living of professionals of Information and Technology sector has improved phenomenally. The size of women professionals at the entry level jobs in I.T. sector is spectacular. Achieving a competitive advantage position and enhancing firm performance relative to their competitors are the main objectives that business organizations in particular should strive to attain. Strategic management can depend upon the size of an organization, and the inclination to change its business environment. The present study aims to identify factors that influence effective strategic planning process in organizations, analyses the key factors that influence strategic planning and explores the reasons for organizations to plan for the future so as to sustain and explores the link between strategic plans with organization structure, organizational culture, leadership and human resources. It is identified that organization success will be achieved by aligning strategic plan with the vision and mission of the organization.